Sanitary Design and Construction of Food Processing and Handling Facilities - Ronald H. Schmidt; Daniel J. Erikson (EDIS)
To ensure safe food and adequate sanitation programs, the facility and surroundings in which food processing and handling operations are conducted must be designed and constructed with sanitary design principles in mind. Many existing facilities do not have optimum sanitary design and construction. Certain adjustments and/or renovations, where feasible, may be necessary. While often discussed separately, sanitary construction and sanitary design are inter-related terminology. This document is FSHN04-08, one of a series of the Food Science and Human Nutrition Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date May 25, 2005.